2014
DOI: 10.1016/j.pec.2013.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues relating to the inclusion of relatives as clients in the post-stroke rehabilitation process as perceived by patients, relatives and health professionals

Abstract: The needs of relatives are well known. The next step is to legitimize their right to receive services and to acknowledge the combined clinical and ethical value of including them post-stroke. Interdisciplinary health care approaches and communication skills should be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…'Role overload' and juggling roles have been described by stroke families as a common poststroke scenario (25), possibly accounting for the lack of control and uncertainty usually reported (8). A comparative study found that established caregivers were sooner able to identify coping strategies than firsttime carers (22), indicating perhaps that prior experience, knowing what to expect, and being able to plan, may help stroke families manage their situation, corroborating our and others' findings (23,24). It was unclear among our participants which constructs (prior caregiving experience, health background/education or personal qualities), individually or collectively, contributed to their preparedness and may be a focus of future research.…”
Section: Being Preparedsupporting
confidence: 84%
See 1 more Smart Citation
“…'Role overload' and juggling roles have been described by stroke families as a common poststroke scenario (25), possibly accounting for the lack of control and uncertainty usually reported (8). A comparative study found that established caregivers were sooner able to identify coping strategies than firsttime carers (22), indicating perhaps that prior experience, knowing what to expect, and being able to plan, may help stroke families manage their situation, corroborating our and others' findings (23,24). It was unclear among our participants which constructs (prior caregiving experience, health background/education or personal qualities), individually or collectively, contributed to their preparedness and may be a focus of future research.…”
Section: Being Preparedsupporting
confidence: 84%
“…For our participants, the hospital environment and medical management of their family member were familiar and they knew where to obtain information and resources, differing from experiences reported by families in other stroke research who described the hospital environment as strange and frightening (19). These other families felt they lacked knowledge and experienced difficulty accessing information (20,21) and their unpredictable circumstances perpetuated uncertainty and anxiety (22,23).…”
Section: Being Preparedmentioning
confidence: 89%
“…Almost all studies reported the data collection process. Thirty studies provided the rationale for their research design, 9, 11, 23, 2527, 29, 3133, 35, 39, 41, 42, 4450, 5254, 58, 62, 65, 66, 70, 71 nine discussed the relationship between researcher and participants, 29, 42, 44, 46, 50, 54, 66, 70, 71 37 reported rigorous data analyses procedures, 4, 7, 9, 11, 24, 2628, 3037, 39, 4146, 4850, 5254, 58, 60, 63, 65, 6770 45 reported the ethical considerations, 4, 7, 9, 2325, 2729, 31, 32, 34, 3650, 5260, 6266, 6871 and 49 reported the recruitment strategy. 7, 9, 11, 2325, 2732, 3463, 6571 Of the 10 quantitative studies appraised using CEBMa, all clearly addressed the research question, methods, selection of participants, and had a sample representing the population.…”
Section: Resultsmentioning
confidence: 99%
“…communication with health care professionals 4, 24, 2628, 3032, 34, 3638, 41, 4446, 4850, 52, 5760, 63, 64, 67, 7375, 82, 83 – “It would have been nice to have somebody sit down with me and say this is what’s happened.” 31 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation